O sujeito trabalhador e o direito internacional social: a aplicação ampliada das normas da Organização Internacional do Trabalho - Pedro Augusto Gravatá Nicoli (2014)
Given the deep crisis in the perimeter of social protection, this thesis proposes a broad applicability of the Conventions of the International Labour Organisation (ILO) to the labor relations in a wide sense, gender of which subordinate employment is the most prominent species in Modernity. An immediate duty emerges for the States to protect, in addition to standard employment, forms of work that are atypical, informal, precarious, performed in own-account, autonomous and independent (but vulnerable) schemes, fragmented in time, whether paid or not, in short, all of the many contemporary expressions of dependence on the direct or indirect alienation of the labor force for the survival of women and men. For this proposition, the study recovers the historical and philosophical construction of work as the object of legal-institutional treatment and of the worker as a legal subject, revealing an alignment between, on the one hand, schemes of denial of work and of the identity of the worker (with the consequent legal exclusion) and, on the other, the reproduction of social risk and poverty. Contemporaneity, in an ambiguous movement of permanence and transformations, strongly affects the dynamics of labor relations with its lines of fragmentation and extreme individualism, in the context of the current strategies of productive restructuring in capitalism. In this context, the expressions of precarious work and the typologies of analysis of the workers, in new classes, are associated with the permanence and expansion of extreme forms of exploitation, resulting in the reproduction of poverty and vulnerability and in the need for a reencounter of Labour Law and the bases of its axiology. This reconnection will result, ultimately, in a broadening movement that is both holistic and anticipatory of possible frustrations in the results, around models that embrace a global project of social justice and that contribute to make of Law an empowering and emancipatory platform for the subject. The extent of this expansive movement embodied in the broad application of ILO standards results finally in the formulation of an International Social Law, arena for the recovery of the integrality of social justice and inclusion as the aims of the political, economic and legal spheres.